Volume 3: Biomedical and Biotechnology Engineering 2018
DOI: 10.1115/imece2018-86009
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Low-Cost Non-Invasive Device to Detect Overnight Hypoglycemia

Abstract: Research in the field of blood glucose monitoring systems has led to incredible advancements over the past several decades. The blood glucose level of a diabetic patient is vital to monitor since large swings in blood sugar can cause life threatening damage to the individual. The importance of blood glucose monitoring increases when a patient experiences hypoglycemia, which can be very dangerous. The objective of this project is to create a low cost portable device that utilizes the modular bio-signal sensor k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study revealed that bioimpedance plays a correcting role in the prediction when paired with other sensors. Bioimpedance of the skin has also been used to detect nocturnal hypoglycemic events ( Lesko et al, 2018 ). Another study investigated the galvanic skin response (GSR) and correlated it with blood glucose levels ( Snekhalatha et al, 2018 ), where a device was developed to acquire the GSR resistance and voltage data from 100 participants (i.e., 50 with diabetes).…”
Section: Non-invasive Sensors and Wearablesmentioning
confidence: 99%
“…The study revealed that bioimpedance plays a correcting role in the prediction when paired with other sensors. Bioimpedance of the skin has also been used to detect nocturnal hypoglycemic events ( Lesko et al, 2018 ). Another study investigated the galvanic skin response (GSR) and correlated it with blood glucose levels ( Snekhalatha et al, 2018 ), where a device was developed to acquire the GSR resistance and voltage data from 100 participants (i.e., 50 with diabetes).…”
Section: Non-invasive Sensors and Wearablesmentioning
confidence: 99%
“…Da Silva et al, e.g., described a development platform aiming at making physiological measurements available “for everyone” [ 1 ]. The group developed the low-cost modular biosignal acquisition hardware platform “BITalino” to enable building biomedical devices in an easier and more reliable way [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Other specially designed hardware for biosignal detection include, e.g., the Olimex shield for ECG and EMG measurements, compatible with Arduino like development boards [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%